Wheat and peanut food allergy in mugwort (Artemesia vulgaris) sensitized patients: A case series of four cases (Indian Journal of Case Reports, 2020)
Non-specific lipid transfer proteins (LTPs) are the major food allergens in mugwort-Pollen Food Syndrome and are associated with systemic allergic reactions. We evaluated the relationship between mugwort pollen with peanut and wheat. The diagnosis was based on a convincing history of an allergic reaction after their food consumption and positive skin prick test with elevated food-specific immunoglobulin E (IgE) by Immunocap. We speculate that the causative allergenic protein Art V3 nsLTP in artemisia, Arh 9 nsLTP in peanut, and Tria 14 nsLTP in wheat are the major allergenic epitopes which are thermostable and resistant to peptic digestion, causing for systemic reaction in our cases.